High prevalence of subclinical energy availability and poor diet quality among paralympic basketball athletes - Urhan, M.; Akanalçi, C.; Küçükerdönmez, Ö.; Karatas, E.; Akder, R. N.; Nalçakan, M.; Meseri, R. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background The aim of this study was to evaluate the pre-season nutritional status, diet quality, and energy availability levels of Paralympic athletes competing in wheelchair basketball.